An analysis of customer change, government support, and cash holdings. (1st September 2021) - Wen, Xuqian; Ye, Yong
This paper uses a research sample listed manufacturing companies in China and systematically studies the impact of customer change and government support on corporate cash holdings and economic consequences. The empirical results show that there is a significant positive correlation between customer change and cash holdings, and the value of cash holdings is higher among enterprises with customer changes. This study enriches and expands the literature on customer relations and cash holdings, and we confirm the important practical significance of government support for the development of the manufacturing industry.